The Mahatma didn’t like the movies and why it matters: Indian broadcasting policy, 1920s–1990s - Jeffrey, Robin (Television in India: Satellites, Politics and Cultural Change, 2008)
This chapter examines the ideological and structural foundations of Indianbroadcasting policy as it developed from the 1930s to the 1990s. The chapter argues that the failure of Indian governments to make the most of radioand television for economic and social development stemmed from threesources: (i) the restrictive policies inherited from a colonial state, (ii) thepuritanism of the Gandhian national movement, and (iii) the fear, madevivid by the 1947 partition, of inflaming social conflict. The policies andinstitutions established in the 1940s and 1950s shaped Indian broadcasting for the next 40 years and have been significantly subverted only since 1992as a result of the transformation effected by satellite television.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé